Spatial Analysis and the Distribution Map of Cigarette Expenditures and Tuberculosis CNR in Indonesia in 2021-2022 - Kurnia, Galuh Mega; Ersanti, Arina Mufida (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2024)
Background: Indonesia is in second place with the highest number of Tuberculosis (TB) cases in the world with a death rate reaching 144,000 cases per year. Smoking has become the second biggest risk factor for TB in Indonesia after poor environmental conditions and Indonesia ranks third with the highest number of smokers in the world. Objective: To analyze the relationship between cigarette expenditure and TB Case Notification Rate in 2021-2022. Method: The study design is an observational quantitative study using secondary data. Mapping was carried out using the QGIS application and spatial analysis was done using the GeoDa application's spatial regression. Results: in 2021 the majority of provinces in Indonesia are in the medium category for average per capita weekly cigarette expenditure and is in the low category for CNR TB. In 2022, most provinces in Indonesia were in the high category for average per capita per week cigarette expenditure and in the medium category for TB CNR. Papua Province needs to get more attention from the government because even though the average cigarette expenditure is low, the TB rate is high. DKI Jakarta Province needs to receive more attention because apart from its high TB rate, the average per capita cigarette expenditure is also high. There’s a relationship between cigarette expenditure and TB CNR in 2021 but not in 2022. Conclusion: There was an increasing trend in cigarette expenditure and TB CNR in Indonesia from 2021 to 2022 and a lack of consistency in the relationship between the two variables from 2021 to 2022.